INTEGRASI SISTEM INFORMASI MANAJEMEN DENGAN TEKNOLOGI BIG DATA DALAM BISNIS - Meisyah Ayu Putri; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The development of the times is becoming more and more sophisticated and everything depends on technology or digital systems which means that every individual or group in running a business must be able to utilize the functions of technology. Every business must be able to maximize the data in its business effectively and efficiently, so that it is easy to take steps or make the right decisions. Management Information Systems are an alternative because Management Information Systems provide Big Data as a solution to the problem of lack of data availability which hinders business people in the development of their companies. The existence of this technology requires companies to be able to build strategic sources of information, because business data information is a very valuable asset for the company. The purpose of this research is how to integrate management information systems in business and utilize big data technology and find out what challenges must be faced. The research method uses a qualitative research approach.